Fairness in the mail and opportunism in the internet: A newspaper experiment on ultimatum bargaining - Werner Güth; Carsten Schmidt; Matthias Sutter (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
On May 11, 2001, readers of the Berliner Zeitung were invited to participate in an ultimatum bargaining experiment played in the strategy vector-mode: Each participant chooses not only how much (s)he demands of the DM 1.000-pie but also which of the nine possible offers of DM 100, 200, ..., 900 (s)he would accept or reject. In addition, participants were asked to predict the most frequent type of behavior. Three randomly selected proposerresponder pairs were rewarded according to the rules of ultimatum bargaining and three randomly chosen participants of those who predicted the most frequent type of behavior received a prize of DM 500. Decisions could be submitted by mail, fax, or via the internet. Behavior is described, statistically analyzed, and compared to usual laboratory ultimatum bargaining results.
urn:nbn:de:kobv:11-10049866
Keywords: C93; 330; fairness; ultimatum bargaining; newspaper (or internet) experiment; distribution conflicts